Media discourse in the digital environment: Misinformation and sustainability challenges - Case study of “Marwa Boughchiche” case during the period from May 24 to July 5, 2025 - HIZIR, Razika (Art Law and Accounting Reporter, 2025)
This study explores the challenges of media sustainability in the digital environment, focusing on the rise of disinformation as a key feature of the post-truth era. Using a qualitative case study approach, it examines the case of Marwa Boughchiche (May 24 – July 5, 2025), which illustrates the shift in media discourse toward rumors and false narratives, particularly on YouTube. The analysis reveals a decline in public trust in both official and unofficial sources, amid a flood of conflicting stories and a lack of clear professional standards for digital content. Findings point to the ethical and institutional fragility of digital media platforms, alongside the growing influence of unqualified content creators. The study concludes that media sustainability goes beyond technical and economic dimensions, requiring a reassertion of ethical and epistemological values. It calls for responsible digital practices that uphold a balance between freedom of expression, information reliability, and the dignity of individuals.
Keywords: media sustainability; disinformation; digital environment; post-truth